A Necessary Condition for Nash Equilibrium in Two-Person Zero-Sum Constrained Stochastic Games. (9th December 2013) - Chang, Hyeong Soo
Abstract : We provide a necessary condition that a constrained Nash-equilibrium (CNE) policy pair satisfies in two-person zero-sum constrained stochastic discounted-payoff games and discuss a general method of approximating CNE based on the condition.